Estilos de aprendizagem e material didático: estudo exploratório com livro de língua inglesa - Freire, Danielle Francine de Pinho (2017)
All human beings are born endowed with the capacity to learn and to teach. At the beginning of the life history of each person and of the culture some people end up developing more certain abilities in detriment of others. The learning styles, according to Alonso, Gallego and Honey (2002), based on Keefe’s definition (1988), "are cognitive, affective and physiological features" since they allow to highlight the differences that each subject brings (Santos, 2013) In order to do this, we use the analyzes of the above-mentioned authors, who conceive the learning styles through four styles: Active, Reflective, Theoretical and Pragmatic. These theorists are recognized in Spanish as percussors in the studies related to learning styles and the elaboration of tests to identify the styles for the educational field, in the case of this study the viability of didactic material produced to attend public school in Brazil. This research aims to demonstrate how the Learning Styles can be worked on in the English language textbook and the proposal of a didactic guide to be used by teachers of the State Education System of the State of Minas Gerais in the final years of Elementary School II, more specifically the 9th grade. We seek to understand how the English language textbook is elaborated, the public policies that guide the adoption of a specific teaching material, as well as describe and analyze a complete textbook unit chosen by the state school researched in order to establish a connection with Learning Styles. The research, of a qualitative nature, is a case study that given its characteristics, allowed to evidence data that made possible to answer the research questions. In order to make the learning of a foreign language more effective we explore the possibility of suggesting a didactic guide based on the knowledge of the profiles of the students and suggest a connection with the Learning Styles, and analyze and propose activities that will attend to the different modes of learning. Learning that are present in the school context, and with this information, teachers and students can create situations and learning environments much more effective.